Whenever you have an equation with your answer as zero, it is possible to have more than one solution. One solution is likely always 0 and the other depends. You write this as; x = (answer), x = (answer)

To start solving this equation, we know that one answer is very likely going to be zero. Zero to any power is always going to be zero. So, x in (2x^3+5x^2) is 0. When you plug in zero, you eventually get 0 + 0 = 0. Next we have to figure out how we can get rid of the 1 in (1-2x). We know that half of two is one and 1 – 1 = 0. So, the value of our second x is 0.5. When you have the whole equation simplified, you get 0 * 0 = 0.

## Answers ( )

Answer:x = 0, x = 0.5

Step-by-step explanation:Whenever you have an equation with your answer as zero, it is possible to have more than one solution. One solution is likely always 0 and the other depends. You write this as; x = (answer), x = (answer)

To start solving this equation, we know that one answer is very likely going to be zero. Zero to any power is always going to be zero. So, x in (2x^3+5x^2) is 0. When you plug in zero, you eventually get 0 + 0 = 0. Next we have to figure out how we can get rid of the 1 in (1-2x). We know that half of two is one and 1 – 1 = 0. So, the value of our second x is 0.5. When you have the whole equation simplified, you get 0 * 0 = 0.

Hope this helps,

Hedgehog68